2013
DOI: 10.1364/ao.52.002735
|View full text |Cite
|
Sign up to set email alerts
|

325 mJ and 46 ns 532 nm Q-switched Nd:YAG laser at 500 Hz

Abstract: A laser diode side-pumped electro-optical Q-switched Nd:YAG green light laser with high repetition rates, short pulse width, and high peak power was demonstrated. We studied the performance of the oscillator at the repetition rates from 100 to 500 Hz. At 500 Hz, 61 mJ, 5 ns of 1064 nm infrared light pulses were obtained with an oscillator-amplifier system. The peak power of the pulse was 12 MW. By frequency doubling with a LiB(3)O(5)(LBO) crystal, 32.5 mJ, 4.6 ns of 532 nm green light was achieved, correspondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The results indicate that further changing the parameters of the resonator, such as pump power and output mirror transmittance, is expected to expand the energy and pulse width range of the output. Additionally, the oscillator shows great potential for application in the field of LIDAR, such as specific band generation (viz., eye-safe, atmospheric window) by combining nonlinear frequency conversion, [17][18][19][20] and single-longitudinal mode generation by using the mode selection technique to improve the coherent detection accuracy. 14,21,22…”
Section: Discussionmentioning
confidence: 99%
“…The results indicate that further changing the parameters of the resonator, such as pump power and output mirror transmittance, is expected to expand the energy and pulse width range of the output. Additionally, the oscillator shows great potential for application in the field of LIDAR, such as specific band generation (viz., eye-safe, atmospheric window) by combining nonlinear frequency conversion, [17][18][19][20] and single-longitudinal mode generation by using the mode selection technique to improve the coherent detection accuracy. 14,21,22…”
Section: Discussionmentioning
confidence: 99%
“…Further characterization of the system revealed that phosphorylated IκB-α actually facilitated DNA exchange by NF-κB (Figure 15), a property that could contribute to its physiological role as a mediator of transcription of numerous cellular genes. 182…”
Section: Modified Ribosomes For Protein Tyrosine Phosphorylationmentioning
confidence: 99%
“…However, its beam quality ( M 2 = 2.5/3.2) is relatively poor due to its side‐pumped scheme. With a frequency doubling crystal, 32.5 mJ, 4.6 ns of 532 nm laser was obtained 13 …”
Section: Introductionmentioning
confidence: 99%
“…With a frequency doubling crystal, 32.5 mJ, 4.6 ns of 532 nm laser was obtained. 13 Thermal management is an essential issue for high energy laser. Longitudinal pumping is one of the most efficient configurations as it could match the mode of the pump beam to the resonant mode.…”
Section: Introductionmentioning
confidence: 99%